Occupational Training for TVET College Civil Engineering Students in the Modern Era: Has Anything Changed? - Mtshali, Thokozani Isaac (Journal of Technical Education and Training, 2021)
Developing and maintaining a definitive list of scarce and essential skills is crucial for the TVET sector. TVET colleges should swiftly work on ‘workplace basics’ skills to attract different industries for their students. The purpose of this study was to inspect how TVET colleges prepare Civil Engineering students with occupational skills relevant for modern engineering era. Descriptive research design was used to describe trends of connection with the help of secondary data. This research design assisted to describe how TVET colleges prepare its Civil Engineering students with occupational skills relevant for modern engineering era. This study adapted Carnevale’s (1990) workplace basics as a conceptual framework. The collective findings revealed that TVET colleges faced several hurdles in their quest to equip Civil Engineering students with the necessary skills that would make them good candidates for taking up employment in industries against the backdrop of changes being wrought by the modern era. Among the recommendations, a call for professional teacher development with focus to 4th industrial revolution skills is made and that SETAs should support that initiative. Also such skills should be intensified in such a way that it may be easy to adapt to the 5th industrial revolution upon its arrival.